2019
DOI: 10.1182/blood-2019-125017
|View full text |Cite
|
Sign up to set email alerts
|

Final Results of a Phase II Biomarker-Driven Study of Ruxolitinib in Relapsed and Refractory T-Cell Lymphoma

Abstract: Introduction: Signaling through JAK1 and/or JAK2 is common among tumor and non-tumor cells within peripheral and cutaneous T cell lymphomas (PTCL and CTCL). We conducted a phase II study of the JAK1/2 inhibitor, ruxolitinib, in patients (pts) with PTCL and CTCL and assessed the predictive value of genetic, immunohistochemical (IHC) and multiparametric immunofluorescence (mIF) biomarkers of JAK/STAT pathway activation for ruxolitinib response. Methods: This is an investigator-initiated multi-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…Toward this end, these discoveries may have an effect on the treatment of these lymphomas. Compounds targeting these vulnerabilities, recently described in some systemic ALCL and other T-cell lymphomas [37,46] should be tested in pre-clinical models, opening the way to the possible design of innovative trials for BIA-ALCL patients and other PTCL subtypes. PDTX are optimal platforms for carrying out pre-clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Toward this end, these discoveries may have an effect on the treatment of these lymphomas. Compounds targeting these vulnerabilities, recently described in some systemic ALCL and other T-cell lymphomas [37,46] should be tested in pre-clinical models, opening the way to the possible design of innovative trials for BIA-ALCL patients and other PTCL subtypes. PDTX are optimal platforms for carrying out pre-clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…A synergistic growth inhibitory effect in NKTCL cell lines was also achieved by a combination of Ruxolitinib with the CDK4/6 inhibitor Ribociclib (LEE011) [ 237 ]. This indicates that Ruxolitinib might not only be efficient in myeloid malignancies, but could also be of therapeutic value for patients with lymphoid malignancies [ 100 , 238 , 239 , 240 , 241 , 242 ]. Clinical trials using Ruxolitinib are ongoing for treatment of different cancer entities, such as HTLV1-associated ATL (NCT01712659), relapsed/refractory ETP-ALL (NCT03613428), relapsed/refractory NK-cell or peripheral T-cell non-Hodgkin Lymphoma (NCT01431209, NCT02974647), and ALL (NCT03117751).…”
Section: When An Immune Cell Becomes Cancerous—hijacking Jakinibs’ Immunosuppressive Side Effects For Treatment Of Nk/t-cell Tumorsmentioning
confidence: 99%
“…A phase II trial of the JAK2 inhibitor ruxolitinib in R/R PTCL and CTCL reported an ORR of 23%, with responses more frequent in the AITL and Nodal Peripheral T-Cell Lymphoma with TFH Phenotype PTCL-TFH) subtypes [63]. Cerdulatinib is a smallmolecule reversible ATP competitive inhibitor of SYK and JAK family members.…”
Section: Jak/stat and Syk Pathway Inhibitorsmentioning
confidence: 99%